A prototypal high-vacuum integrated collector storage solar water heater: Experimentation, design, and optimization through a new in-house 3D dynamic simulation model. (1st January 2022) - Barone, G.; Buonomano, A.; Palmieri, V.; Palombo, A.
Abstract: Integrated collector storage units are typically affected by convective and radiative heat losses which significantly reduce their energy performance. To enhance solar collection and heat retention, innovative techniques and novel design of such units are being more and more developed. In this framework, this paper focuses on the design and optimization of a prototypal high-vacuum integrated collector storage solar water heater. The proposed unit allows for reaching high temperatures of the stored water and for reducing the temperature drop during non-collection periods. This goal is achieved by suppressing the convective heat losses into the system by keeping the pressure into the related enclosure below 0.01 Pa and by applying a special selective coating to the solar absorber surface to drastically reduce radiative losses as well. In this paper, details about the system design and the conducted experimental tests are reported. In addition, a new mathematical model able to assess the energy performance of the innovative prototype is presented. This tool, based on a detailed 3-D transient finite-difference thermal network, was validated against the gathered experimental data. By such a tool the optical properties of the adopted selective coating are optimized for maximizing the system thermal efficiency. Finally, with the twofold aim of showing the potentiality of the developed code, as well as the effectiveness of the presented innovative solar collector prototype, a comprehensive case study referred to three different European weather zone is presented. Promising results in terms of energy savings (0.73 MWh/y) and CO2 emission reduction (149 kgCO2 /y) are achieved. Highlights: A prototypal high-vacuum Integrated Collector Storage Solar Water Heater is presented. To cut thermal losses a high-vacuum level is achieved by a non-evaporable getter pump. A 3D thermal model of the prototypal unit is developed and experimentally validated. A case study analysis is conducted to show the potentials of the proposed collector. The collector exhibits remarkable primary energy savings ranging from 33 to 62%.